Spanish wastewater reveals the current spread of Monkeypox virus. (1st March 2023) - Girón-Guzmán, Inés; Díaz-Reolid, Azahara; Truchado, Pilar; Carcereny, Albert; García-Pedemonte, David; Hernáez, Bruno; Bosch, Albert; Pintó, Rosa María; Guix, Susana; Allende, Ana; Alcamí, Antonio; Pérez-Cataluña, Alba; et al.
Highlights: Aluminum-based precipitation used for wastewater surveillance of SARS-CoV-2 works for MPXV. MPXV DNA was detected by qPCR in longitudinal samples collected from several Spanish WWTPs. WBE is a sensitive and cost-effective strategy for the surveillance of MPXV. Summary: Besides nasopharyngeal swabs, monkeypox virus (MPXV) DNA has been detected in a variety of samples such as saliva, semen, urine and fecal samples. Using the environmental surveillance network previously developed in Spain for the routine wastewater surveillance of SARS-CoV-2 (VATar COVID-19), we have analyzed the presence of MPXV DNA in wastewater from different areas of Spain. Samples ( n = 312) from 24 different wastewater treatment plants were obtained between May 9 (week 19 of 2022) and August 4 (week 31 of 2022). Following concentration of viral particles by a validated aluminum adsorption-precipitation method, a qPCR procedure allowed us to detect MPXV DNA in 56 wastewater samples collected from May 16 to August 4, 2022, with values ranging between 2.2 × 10 3 to 8.7 × 10 4 genome copies (gc)/L. This study shows that MPXV DNA can be reproducibly detected by qPCR in longitudinal samples collected from different Spanish wastewater treatment plants. According to data from the National Epidemiological Surveillance Network (RENAVE) in Spain a total of 6, 119 cases have been confirmed as of August 19, 2022. However, and based on the wastewater data, the reported clinical cases seem to be underestimated and asymptomatic infections may be more frequent than expected. Graphical abstract: Image, graphical abstract